2003
DOI: 10.1113/eph8802532
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hypervolaemia Improves Arterial Oxygen Pressure in Athletes with Exercise‐Induced Hypoxaemia

Abstract: The aim of this study was to determine the effect of acute plasma volume expansion on arterial blood-gas status during 6.5 min strenuous cycling exercise comparing six athletes with and six athletes without exerciseinduced arterial hypoxaemia (EIAH). We hypothesized that plasma volume expansion could improve arterial oxygen pressure in a homogeneous sample of athletes -those with EIAH. In this paper we have extended the analysis and results of our recently published surprising findings that lengthening cardiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
3

Year Published

2004
2004
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 35 publications
3
9
3
Order By: Relevance
“…1, 2, 3, 4) mirrored data reported previously reported (Manohar et al 2001a(Manohar et al , b, 2002a(Manohar et al , b, 2003(Manohar et al , 2004. The present study was carried out to determine whether, similar to observations in human athletes (Zavorsky et al 2003), preexercise induction of acute hypervolemia would improve arterial oxygenation in thoroughbred horses performing maximal exercise. In this context, our data revealed that acute pre-exercise expansion of plasma volume did not offer an advantage in significantly modifying the development and/or severity of arterial hypoxemia and desaturation of hemoglobin ( Fig.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…1, 2, 3, 4) mirrored data reported previously reported (Manohar et al 2001a(Manohar et al , b, 2002a(Manohar et al , b, 2003(Manohar et al , 2004. The present study was carried out to determine whether, similar to observations in human athletes (Zavorsky et al 2003), preexercise induction of acute hypervolemia would improve arterial oxygenation in thoroughbred horses performing maximal exercise. In this context, our data revealed that acute pre-exercise expansion of plasma volume did not offer an advantage in significantly modifying the development and/or severity of arterial hypoxemia and desaturation of hemoglobin ( Fig.…”
Section: Discussionsupporting
confidence: 85%
“…This is in contrast with findings in hyperhydrated horses, wherein arterial oxygen tension during exertion either decreased significantly (Sosa-Leon et al 2002) or remained unaffected (Manohar et al 2003). Although the reasons for divergent findings regarding the effects of hypervolemia on the exercise-induced arterial hypoxemia in human athletes (Zavorsky et al 2003) versus horses (Sosa-Leon et al 2002;Manohar et al 2003) are unclear, it is plausible that the divergent methodologies used for the induction of hypervolemia may have played a role. In this context, whereas hyperhydration in the equine studies (Sosa-Leon et al 2002;Manohar et al 2003) was induced gradually over several hours following nasogastric administration of salt/fluids-which may have allowed H 2 O equilibration across various compartments-hypervolemia in the human athletes was induced rather acutely upon rapid osmotic absorption of water from tissues into the vascular compartment following intravenous (IV) administration of 10% pentastarch (Zavorsky et al 2003).…”
Section: Introductioncontrasting
confidence: 56%
See 3 more Smart Citations